The use of infrared spectroscopy and thermal analysis for the quick detection of adulterated beeswax. Issue 4 (7th August 2020) - Miłek, Michał; Drogoń, Agata; Pyda, Marek; Czerniecka-Kubicka, Anna; Tomczyk, Monika; Dżugan, Małgorzata
Abstract : Beeswax samples of different origins were evaluated for their authenticity by infrared spectroscopy and thermal analysis. The Fourier Transform Infrared Spectroscopy (FT-IR) method was used for the genuineness assessment and the melting process was examined using the differential scanning calorimetry (DSC) method. Eight suspicious beeswax samples delivered by local beekeepers were examined. As reference standards, pure authentic beeswax standards, pure paraffin, and wax-paraffin blends were used. The comparison of the infrared spectra of tested wax samples and references allowed the identification of adulterated wax samples based on the differences in the spectra fingerprint region (700 to 1800 cm −1 ), especially 1170 and 1735 cm −1 bands. Moreover, the ratio of the 1735 and 2850 cm −1 band area (lower than 0.5) was used as an indicator of wax adulteration. Among the 8 samples studied, 3 were found to have been falsified with paraffin. The thermal analysis confirmed the adulteration of the same wax samples. The melting temperatures determined in these cases were lower (52.3 to 57.7) as compared to other samples (63.1 to 65.9), identified as real beeswax by comparison to standards (63.8 to 64.7). A similar tendency during the re-heating of cooled wax samples was observed, which suggested the addition of paraffin or another substance with a lower melting point to adulterated waxes. The methods used in this research (FT-IR and DSC) allowed for a relatively quick, easy, and inexpensive verification of the authenticity of the beeswax. Such a method can be used as a screening step before a comprehensive GC analysis of beeswax.